Effect of Feeding Sugarcane Byproduct Based Ration on Growth and Carcass Traits of Male Buffalo Calves - Kumar, R. Prasanna; Kumar, M. Shashi; Rani, Sahitya (Journal of Meat Science, 2014)
An experiment was conducted to study the effect of feeding sugarcane byproduct based ration on growth, nutrient utilization and carcass characteristics of male buffalo calves. Six rations which includes five complete rations (CR-I to CR-V) and one conventional ration as control were studied. Highest average daily gain (ADG) (610.0g) was recorded in buffalo bull calves fed on complete ration-II (Sugarcane tops, maize stover and balanced concentrate mixture) when compared among the complete rations and control. The cost of production per kg live weight gain was Rs.41.14 in control group. The cost of production per kg live weight gain was insignificantly higher in control than complete rations. The cost of production per kg live weight was reduced by Rs.3.11, 8.69, 8.60, 10.92 and 8.10 for complete rations-I, II, III, IV and V, respectively, when compare to control diet. The dressing percentage on live weight was significantly (P
Keywords: Sugarcane by-products; Murrah buffaloes males calves; Growth; Meat production; Carcass characteristics